Sekolah Efektif dalam Konteks Manajemen Berbasis Sekolah (MBS) - Saepulloh, Maman (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
Effective schools are a key indicator of educational success, which is not only determined by academic achievement but also by the quality of overall school management. Along with the decentralization policy in education, School-Based Management (SBM) has become a strategic approach to improving school effectiveness through autonomy, participation, transparency, and accountability. This study aims to comprehensively examine the concept of effective schools in the perspective of SBM, including the characteristics of effective schools, factors influencing school effectiveness, the relationship between effective schools and SBM, as well as the challenges and strategies of its implementation. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analysis in several schools in Bogor Regency that have implemented SBM. The results indicate that effective schools in the context of SBM are characterized by strong principal leadership, active participation of the school community and society, professional support for teachers, a positive school culture, and efficient resource management. The main challenges in implementing SBM include budget limitations, resistance to change, and the need for continuous training. With appropriate strategies, SBM is proven to be able to improve school effectiveness in a sustainable manner.